Influence of flow with suspended particles on temperature fields and convective heat transfer - Aydin, M (2012)
The present paper reports the results of a numerical study of forced convection heat transfer between two plates filled with particles. We study the influence of particles suspended in flows on heat transfer enhancement. We consider steady-state fluid flow between two flat horizontal parallel plates with both plates kept at the same temperature. Mono-disperse particles with low and high thermal conductivities injected at the entrance are entrained with the flow. Their effects on temperature field and convective heat transfer are determined from the flow field.